Can health systems platforms do more for nutrition in India? Insights on missed opportunities from India's National Family Health Survey, 2015–2016 - Nguyen, Phuong Hong; Menon, Purnima; Avula, Rasmi; Tran, Lan Mai; Kumar, Alok; Baswal, Dinesh; Sethi, Vani; Hajeebhoy, Nemat; Ranjan, Alok (American Society for Nutrition, 2020)
Most nutrition interventions can be delivered through health systems. However, the progress to scale up effective nutrition interventions and achieve universal health coverage has not been uniform. We aimed to 1) examine the opportunity gaps (OGs) between delivery platforms and corresponding nutrition interventions through the continuum of care (from pregnancy up to early childhood) in India between 2006 and 2016; and 2) assess inequalities in these OGs.